Patrera longipes - Oliveira, Luiz Fernando M.; Brescovit, Antonio D. (Zenodo, 2021)
Patrera longipes (Keyserling, 1891) Figs 4A–G; 5A–D; 6A–I; 27B Anyphaena longipes Keyserling, 1891: 91, figs 53–53a (Syntypes, one male from Rio Grande (32°2’6”S; 52°5’56”W), Rio Grande do Sul, Brazil, von Ihering leg., deposited in BMNH 1890.7.1.624 and five females and one loose male palp, from Nova Friburgo, Rio de Janeiro, Brazil, deposited in BMNH 1890.7.1.625-628, all examined. Lectotype male in BMNH 1890.7.1.624 and paralectotypes in BMNH 1890.7.1.625-628 here designated). Teudis longipes : Petrunkevitch, 1911:517; Mello-Leitão, 1943: 240. Teudis itatiayae Mello-Leitão, 1915: 139 (Holotype female from Retiro [Retiro do Ramos, Parque Nacional do Itatiaia, circa 2200 m], Itatiaia, Rio de Janeiro, Brazil, 1903, C. Moreira leg., deposited in MNRJ 182, examined, lost in the 2018 fire); Silva-Moreira et al. , 2010: 13. New synonymy . Sillus delicatus Mello-Leitão, 1922: 35 (Syntypes male and female from Pinheiro (currently Piraí, Pinheiral), C.F. de Mello- Leitão leg., deposited in the MNRJ 654, examined, lost in the 2018 fire); Silva-Moreira et al. , 2010: 12. New synonymy . Sillus spinifrons Mello-Leitão, 1926: 11, fig 11 (Syntypes two females from Caxambú, Minas Gerais, Brazil, C.F. de Mello- Leitão leg., deposited in the MNRJ 665, not examined, lost); Silva-Moreira et al. , 2010: 3 (Syn.). Patrera longipes : Brescovit, 1997: 33; Silva-Moreira et al. , 2010: 3, 12. Synonymy. The loose palp, here considered as a male paralectotype, corresponds to that of the lectotype. Despite the distance between the records, there are females from the same location, confirming co-specificity. In relation to the synonymies, the description of Mello-Leitão (1922) points out that Sillus delicatus has a curved black crossbeam in the middle of the abdomen, which folds to the anterior region at the ends, in two short longitudinal branches. This same band occurs ventrally in the abdomen of Teudis itatiayae and in Patrera longipes (both types examined), allowing the synonymy between these three species. Other material examined. BRAZIL. Goiás : Barro Alto (14°58’15”S; 48°54’57”W), Região do Rio São Francisco, 1♂, 03.V.1935, J. Blaser leg. (IBSP 419); Bahia : Itamaraju (17º02’21”S; 39º31’52”W), 4♂, 2♀, VII.1994, A. T. Costa leg. (IBSP 35038); Fazenda Pau Brasil (17°2’20”S; 39°31’51”W), 1♀, 26.X.1970, Equipe CEPLAC leg. (IBSP 15323); 18♂, 5♀, 1970 (MNRJ 3014; MNRJ 3189; MNRJ 1340; MNRJ 3189; MNRJ 13332), 1♂ (MNRJ 2455); all collected in 1970 by Cepec / Ceplac; Jussari (15°11’27”S; 39°29’42”W), 4♂, 1970, Cepec / Ceplac leg. (MNRJ 3147); Minas Gerais : Belo Horizonte, Parque Fazenda Lagoa do Nado (19°49’52”S; 43°57’43”W), 1♂, 30.X.1993, A.J. Santos leg. (IBSP 36227); Catas Altas, Reserva Particular do Patrimônio Natural da Serra do Ca- raça (20°5’53.6”S; 43°29’17”W), 1♀, 12.I.2002, E.S.S. Álvares leg. (IBSP 55728); Caxambú (21°58’37”S; 44°55’58”W), 3♀, [without date] (MNRJ 633; MNRJ 655); Espírito Santo : Domingos Martins (20º21’48”S; 40º39’33”W), 1♀, I.1991, R. Bertani leg. (IBSP 7436); Rio de Janeiro : Teresópolis, Parque Nacional da Serra dos Órgãos (22°29’35”S; 43°4’24”W), 1♂, 1♀, 18–31.XII.2011, R.P. Indicatti & B. Gambaré leg. (IBSP 219374); Petrópolis, Fazenda Ranchinho da Roça (22°30’18”S 43°10’44”W), 1♂, 4♀ (IBSP 139933; IBSP 139938; IBSP 139939; IBSP 139941; IBSP 139943), all collected in 08–15.II.2000 by Equipe Biota; Nova Friburgo (22°16’55”S; 42°31’51”W), 2♀, [without date] (MNRJ 18339; MNRJ 41420); Rio de Janeiro (22°57’47”S; 43°14’40”W), Serra da Carioca, 1♂, 1♀, XII.2002, E. Wienskoski leg. (IBSP 38349); Parque Laje (22°57’37.98”S; 43°12’43.34”W), 1♂, 19.X.1991, R.L.C. Baptista leg. (MZSP 14110); Represa do Rio Grande, Serra de Bangu (22°54’20”S; 43°28’14”W), 1♂, I.1967, M. Alvarenga leg. (MZSP 14111); Cachoeiras de Macacu, Reserva Ecológica de Gua- piaçu (22°35’14.61”S; 42°56’24.69”W), 4♂ (IBSP 138966; IBSP 138982; IBSP 138983; IBSP 139002), all col- lected in 08–12.X.2001 by Equipe Biota; Angra dos Reis (23°0’36”S; 44°19’6”W), Ponta da Aripeba, 1♂, 13– 16.XI.1993, A.B. Bonaldo leg. (IBSP 221069); Itatiaia, Parque Nacional do Itatiaia (22º27’10,944”S; 44º36’38.543”W), 1♂, 01–09.I.2014, R.P. Indicatti & B. Gambaré leg. (IBSP 169424); 1♀, I.1998, R.L.C. Baptista leg. (MNRJ 3230); São Paulo : Itapetininga, Estação Ecológica de Angatuba (23º24’00”S; 48º21’00”W), 3♂, (IBSP 138702; IBSP 138708; IBSP 138712), all collected by 11–16.XI.2002 by Equipe Biota; Itú (23°15’50”S; 47°17’56”W), Fazenda Pau D’Alho, 2♂, 2♀, 02.II.1959, F. Lane leg. (AMNH); Pindamonhangaba (22º55’26”S; 45º27’42”W), 1♂, 15.XII.1994, R. Martins leg. (IBSP 5902); São Pedro, Ribeirão Vermelho (20°28’19”S; 45°07’27”W), 1♂, 5♀, XII.1945, A.Zamith leg.(IBSP212660); Limeira (22°33’54”S; 47°24’7”W), 1♀, 17.XII.1951, W.C.A. Bokermann leg. (MZSP 12283); Jundiaí, Reserva Biológica Municipal da Serra do Japi (23°12’00”S; 46º30’00”W), 1♂, 08.XII.1997, A.J. Santos leg. (IBSP 15363); 1♀, I.1999, A.J. Santos leg. (IBSP 37541); 1♀, 2008–2009, C. Vieira leg. (IBSP 140752); Atibaia (23°35’30”S; 48°3’11”W), Parque Municipal da Serra de Itapetininga, 1♀, 04.II.2000, A.J. Santos leg. (IBSP 37523); São Paulo, Campus USP, Reserva Florestal da CUASO (23º33’00”S; 46º43’00”W), 2♂, 10♀, 14.XII.1999 – 01.II.2001, (IBSP 29402–IBSP 29411; IBSP 30116; IBSP 32931), all collected by F.S. Cunha, J. Império, R.P. Indicatti & D.F. Candiani; Campus Instituto Butantan (23º33’00”S; 46º43’00”W), 1♂, 11.XI.2004, no coll. (IBSP 215374); Campus Instituto Butantan, Horto Oswaldo Cruz, 1♀, V.2000 – II.2001, D.F. Candiani leg. (IBSP 76235); Parque Estadual Fontes do Ipiranga (23°38’24.6”S; 46°37’3.1”W), 1♀, 20.I.2018, Z.R. Mendes leg. (IBSP 222762); Santo André, Reserva Biológica do Alto da Serra de Paranapiacaba (23º46’00”S; 46º18’20”W), 3♂, 14–16.XII.2003, C.A. Rheims & R.P. Indicatti leg. (IBSP 52098); Parque Duque de Caxias (currently Parque Celso Daniel) (23°38’50”S; 46°32’9”W), 1♀, 2004, A. Macedo leg. (IBSP 75194); Mauá, Gruta de Santa Luzia (23°40’00”S; 46°24’00”W), 1♀, 2004, A. Macedo leg. (IBSP 62726); São Caetano, Parque Chico Mendes (23°37’57”S; 46°34’23”W), 1♀, 2004, A. Macedo leg. (IBSP 75138); Salesópo- lis, Estação Biológica de Boracéia (23°37’53”S; 45°52’13”W), 1♀, 13–17.III.2007, F V. Yamamoto leg. (IBSP 79028); 1♀, 28.II–03.III.1992, R.L.C. Baptista leg. (IBSP 212904); Biritiba Mirim, Barragem do Rio Biritiba (23°36’12.143”S; 46°5’13.654”W), 1♀, V.2003 (IBSP 117540); 2♀, V.2003 (IBSP 122416), all collected by Equipe IBSP; Peruíbe, Estação Ecológica Juréia-Itatins (24°28’59”S; 47°10’39”W), Núcleo Arpoador, 1♂, 02.II.1997, R. Bertani leg. (IBSP 7784); Ubatuba, Parque Estadual Ilha Anchieta (23º32’00”S; 45º03’00”W), 3♂, 1♀ (IBSP 138616; IBSP 138619; IBSP 138622; IBSP 138623), all collected in 23–30.VII.2001 by Equipe Biota; Mogi das Cruzes, Parque Natural Municipal da Serra do Itapety (23°12’00”S; 46°30’00”‘W), 1♂, 13–19.X.2003, Equipe Biota leg. (IBSP 139481); Ilhabela (23°48’54”S; 45°22’14”), Ilha da Vitória, 1♀, III.1964, Expedição do Museu de Zoologia leg. (MZSP 14135); Paraná : Ponta Grossa, Parque Estadual de Vila Velha (25°14’17”S; 50°0’39”W), 1♂, 15.XII.1986 (IBSP 221071); 2♂, 29.XII.1986 (IBSP 221080); 1♀, 03.XI.1986 (IBSP 221083); 1♀, 05.I.1987 (IBSP 22110), all collected by Equipe CIIF; Pinhão, Rio dos Touros, UHE de Segredo (25°47’35”S; 52°6’47”W), 1♂, 21.XI.1991, R. Pinto da Rocha & A.P. Barreto leg., am. 134 (MHCI); 1♂, am. 156 (MHCI); Curitiba (25°25’47”S; 49°16’19”W), 1♂, [without date], Rohr leg. (MNRJ 18352); Santa Catarina : Bombinhas, Reserva Biológica Marinha da Ilha do Arvoredo (27°17’57”S; 48°21’23”W), 1♀, 3–7.V.1995, A.A. Lise et al. leg. (MCTP 6295); Blumenau, Parque Natural Municipal Nascentes do Garcia (27º01’00”S; 49º09’00”W), 1♀, 21–28.I.2003, Equipe Biota leg. (IBSP 139679); Seara (27°8’56”S; 52°18’39”W), Nova Teutônia, 1♂, [without date], F. Plaumann leg. (FMS 13600); Paulos Lopes, Parque Estadual da Serra do Tabuleiro (27°52’27”S; 48°49’26”W), 4♂, 3♀ (IBSP 139714; IBSP 140039; IBSP 140040; IBSP 140053; IBSP 140062; IBSP 140075; IBSP 140098), all collected in 10–20.I.2003 by Equipe Biota; Rio Grande do Sul : Arroio Grande, Mata Ciliar do Rio Piratini (31°54’06.47”S; 52°39’08.29”W), 1♀, 20.XII.2007 (MCN 54543); 1♀, 30.I.2008 (MCN 54594); 1♂, 19.XII.2008 (MCN 54867); 1♂, 14.II.2009 (MCN 54883); all collected by E.N.L. Rodrigues & P.E.S. Rodrigues; Cristal (31°0’10”S; 52°3’0” W), Rio Camaquã, 1♂, 19.XII.2007, E.N.L. Rodrigues leg. (MCN 48624); 2♀, 03.II.2008, E.N.L. Rodrigues leg. (MCN 48639); Mata Ciliar do Rio Camaquã, 1♀, 18.XII.2008, E.N.L. Rodrigues & P.E.S. Rodrigues leg. (MCN 53745); 1♀, 23.III.2009, E.N.L. Rodrigues & P.E.S. Rodrigues leg. (MCN 53799); Maquiné, Fepagro (29º39’00”S; 50º12’00”W), 5♂, 4♀ (IBSP 139184; IBSP 139202; IBSP 139210; IBSP 139229; IBSP 139238; IBSP 139249; IBSP 215376), all collected in 18–27.I.2002 by Equipe Biota; Derrubadas, Parque Estadual do Turvo (27°8’44”S; 53°53’10”W), 2♂, 2♀, 11–18.I.2002, Equipe Biota leg. (IBSP 140030); Maquiné (29°40’30”S; 50°12’25”W), 1♂, 12.XII.2007, L. Moura & R. Moraes leg., (MCN 43766); Maquiné, (29°40’30”S; 50°12’25”W), Mata Ciliar do Rio Maquiné, 1♀, 17.XII.2007, E.N.L. Rodrigues & P.E.S. Rodrigues leg. (MCN 54113); 1♀, 28.XII.2008, E. N.L. Ro- drigues & P.E.S. Rodrigues leg. (MCN 54357); Rio Maquiné, 1♂, 27.I.2008, E.N.L. Rodrigues leg. (MCN 48435); Machadinho (27°34’01”S; 51°40’04”W), 1♂, 1♀, 11.XII.1980, A.A. Lise leg. (IBSP 258335); Santa Maria, Camo- bi, Cidade dos Meninos (29°42’7,77”S; 53°43’16.07”W), 1♂, 18.XII.1997, L. Indrusiak & M. Monteiro leg. (IBSP 120124); 1♂, 19.XII.1997, L. Indrusiak & M. Monteiro leg. (IBSP 214327); Palmares do Sul, Ilha Grande, Lagoa do Casamento (30°20’10”S; 50°37’46”W), 1♀, 09.IV.2003, Equipe Probio leg. (MCN 35447); Parobé (29°37’44”S; 50°50’06”W), Rio dos Sinos, 1♀, 25.XII.2008, E.N.L. & P.E.S. Rodrigues leg. (MCN 47864); Triunfo (29°56’34”S; 51°43’4”W), 1♀, 25.XI.1994, L. Moura leg. (IBSP 212645); São Leopoldo (29º45’36”S; 51º08’49”W), 1♂, 17.XII.1986, C.J. Becker leg. (IBSP 221100); Campo Bom (29º40’44”S; 51º03’10”W), 3♂, 14.XII.1987, C.J. Beck- er leg. (IBSP 221102); Viamão (30°04’51”S; 51°01’22”W), 2♂, 25.XI.1994 (MCTP 5825); 1♂, 25.XI.1994 (MCTP ex. 5790); all collected by A.A. Lise et al. Gravataí, Morungava (29°51’48”S; 50°52’33”W), 1♀, 02.II.1992, A.D. Brescovit leg. (IBSP 221099). ARGENTINA. Misiones : San Pedro, Refugio Piñalito (26°30’00”S; 53°50’00”W), 1♂, I.1954, M.E. Galiano & R.D. Schiapelli leg. (MACN-Ar). Diagnosis. Males of Patrera longipes are easily distinguished from the remaining species by the tibial retrolateral apophysis very large and rounded at tip with shovel-shaped, and by the conspicuous prolateral posterior cymbial projection (Figs 4D, E, 5B, 6D–H) in the male palp. Females are diagnosed by the broad atrium, wider than long, and by the triangular, large hood in the anterior area of the epigynal plate (Figs 5C, 6I). Description. Male (Holotype). Carapace orange. Chelicerae brown yellowish, labium and endites orange. Sternum orange, with dark borders. Legs yellowish orange. Abdomen dorsally brownish, ventrally grayish cream, with dark gray band transversely at the median region (close to the tracheal spiracle). Spinnerets whitish (Fig. 4A). Total length 5.5, carapace length 2.3, width 1.8. Clypeus height 0.08. Eye diameters and interdistances: AME 0.08, ALE 0.15, PME 0.15, PLE 0.15; AME–AME 0.05, AME–ALE 0.05, PME–PME 0.15, PME–PLE 0.12, ALE–PLE 0.07. Chelicerae 1.2 long, six promarginal teeth, four retromarginal denticles (Fig. 6A). Leg measurements: leg I—femur 3.6/ patella 1.1/ tibia 4.0/ metatarsus 3.35/ tarsus 1.35/ total 13.4; II—3.45/ 1.05/ 3.55/ 3.0/ 1.2/ 12.25; III—2.25/ 0.7/ 1.9/ 2.15/ 0.7/ 7.7; IV—3.5/ 0.9/ 3.3/ 3.4/ 1.2/ 12.3. Leg spination: I—II—tibia v2-2-0, p1-1-1, r1-1-1, metatarsus v2-1-0, p1-1-1, r1-1-1; III—IV—tíbia v2-2-2, p1-1-0, r1-1-0, metatarsus v2-2-2, p1-1-1, r1-1-1. Abdomen: length 3.25, epigastric furrow 2.05 from tracheal spiracle, spiracle 2.35 from base of spinnerets. Palp: tibia as long as cymbium, slightly curved; cymbium with small ventral basal projection; oval tegulum, with sperm duct running along the basal border; tegular projection with rounded apex, prolaterally positioned; short, curved median apophysis; longitudinally grooved embolus, with prolateral origin, curved medially over the tegulum and projecting toward the apex of the cymbium (Figs 4C, 5A, 6B, D, E). Female (BMNH 1890.7.1.625). Coloration as in male, except dorsal abdomen, lighter (Fig. 4B). Total length 7.4, carapace length 2.8, width 2.25. Clypeus height 0.06. Eye diameters and interdistances: AME 0.08, ALE 0.17, PME 0.17, PLE 0.17; AME–AME 0.05, AME–ALE 0.05, PME–PME 0.13, PME–PLE 0.12, ALE–PLE 0.06. Chelicerae 1.17 long, eight promarginal teeth, four retromarginal denticles. Leg measurements: leg I—femur 4.1/ patella 1.15/ tibia 4.35/ metatarsus 3.65/ tarsus 1.6/ total 14.85; II—3.86/ 1.05/ 3.9/ 3.35/ 1.25/ 13.4; III—2.65/ 0.9/ 2.05/ 2.6/ 0.7/ 8.9; IV—3.9/ 1.1/ 3.5/ 3.9/ 1.1/ 13.5. Leg spination: I— II—tibia v2-2-0, p0, r0, metatarsus v2-0-0, p0, r0; III—tibia v2-2-0, p1-1-0, r1-1-0, metatarsus v2-2-2, p1-1-1, r1-1-1; IV—tibia v2-2-2, p1-1-0, r1-1-0, metatarsus v2-2-2, p1-1-1, r1-1-1. Abdomen: length 4.65, epigastric furrow 1.5 from tracheal spiracle, spiracle 1.7 from base of spinnerets. Epigynum: lateral borders narrow, not connected distally, medially projected over the atrium; internally with long, coiled copulatory ducts; elongated seminal receptacles, in the proximal area of the copulatory ducts; reniform spermathecae; fertilization ducts as long as the spermathecae, curved, basal (Figs 4F, G, 5C, D, 6I). Variation. Males (n=10): total length 5.5–7.5; carapace length 2.3–3.0; femur I length 3.6–5.2; Females (n=10): total length: 7.2–8.4; carapace length 2.7–3.2; femur I length 3.8–4.7. Distribution . Midwest, Southeast and South of Brazil and Northeastern Argentina (Fig. 27B). : Published as part of Oliveira, Luiz Fernando M. & Brescovit, Antonio D., 2021, The spider genus Patrera Simon (Araneae: Dionycha, Anyphaeninae) in the Atlantic Forest biome, with the description of one new species from Brazil, pp. 201-246 in Zootaxa 4991 (2) on pages 210-215, DOI: 10.11646/zootaxa.4991.2.1, http://zenodo.org/record/5028185 : {"references": ["Keyserling, E. (1891) Die Spinnen Amerikas. Brasilianische Spinnen. Vol. 3. Bauer & Raspe, Nurnberg, 278 pp.", "Petrunkevitch, A. (1911) A synonymic index-catalogue of spiders of North, Central and South America with all adjacent islands, Greenland, Bermuda, West Indies, Terra del Fuego, Galapagos, etc. Bulletin of the American Museum of Natural History, 29, 1 - 791. https: // doi. org / 10.5962 / bhl. title. 23819", "Mello-Leitao, C. F. de (1943) Catalogo das aranhas do Rio Grande do Sul. Arquivos do Museu Nacional do Rio de Janeiro, 37, 147 - 245.", "Mello-Leitao, C. F. de (1915) Alguns generos e especies novas de araneidos do Brasil. Broteria, Series Zoology, 13, 129 - 142.", "Silva-Moreira, T. da, Baptista, R. L. C., Kury, A. B., Giupponi, A. P. L., Buckup, E. H. & Brescovit, A. D. (2010) Annotated check list of Arachnida type specimens deposited in the Museu Nacional, Rio de Janeiro. II - Araneae. Zootaxa, 2588 (1), 1 - 91. https: // doi. org / 10.11646 / zootaxa. 2588.1.1", "Mello-Leitao, C. F. de (1922) Novas clubionidas do Brasil. Archivos da Escola Superior de Agricultura e Medicina Veterinaria, Rio de Janeiro, 6, 17 - 56.", "Mello-Leitao, C. F. de (1926) Algumas aranhas do Brasil meridional. Boletim do Museu Nacional do Rio de Janeiro, 2, 1 - 18.", "Brescovit, A. D. (1997) Revisao de Anyphaeninae Bertkau a nivel de generos na regiao Neotropical (Araneae, Anyphaenidae). Revista Brasileira de Zoologia, 13, 1 - 187. https: // doi. org / 10.1590 / S 0101 - 81751996000500001"]}